Talk or Text? The Role of Communication Modalities in the Adoption of a Non-directive, Goal-Attainment Coaching Chatbot - Terblanche, N H D; Wallis, G P; Kidd, M (Interacting with computers, 2023)
Abstract Despite the proliferation of chatbots (conversational agents) in increasingly varied contexts, user satisfaction with chatbot interactions remains a challenge. We do not yet fully understand chatbot usability and adoption factors or how to customize chatbots based on users' personality traits. One important and under researched aspect of chatbot design is users' perceptions of different communication modalities such as voice and text. In this between-group study (n = 393 participants), we asked participants to rate an equivalent text-based (n = 189) and voice-based (n = 204) non-directive, goal-attainment coaching chatbot in terms of usability, performance expectancy and risk perception. We also considered participants' personality in terms of extraversion. For usability across all participants, there was no difference between the chatbots for all participants; however, a higher rating of the voicebot was observed in the group classified as introverts and no difference was found for participants classified as extroverts. For performance expectancy all participants, extroverts and introverts rated the textbot higher. Risk ratings showed no difference between bots for all participants, extroverts and introverts. The results suggest that the voicebot was considered slightly easier to use for some participants while the textbot was considered to perform better by all participants. Creators of chatbots should consider using voice as a modality to attract users and text as a mode to accomplish complex tasks. Extraversion did not play a significant part in chatbot communication modality choice. These results may assist in designing context and audience-specific chatbots for increased efficacy and user satisfaction.